Air-Sea CO2-Exchange in a Large Annular Wind-Wave Tank and the Effects of Surfactants - Ribas-Ribas, Mariana; Helleis, Frank; Rahlff, Janina; Wurl, Oliver (Frontiers in Marine Science, 2018)
Wind, chemical enhancement, phytoplankton activity, and surfactants are potential factors driving the air-sea gas exchange of carbon dioxide (CO2). We investigated their effects on the gas transfer velocity of CO2 in a large annular wind-wave tank filled with natural seawater from the North Atlantic Ocean. Experiments were run under 11 different wind speed conditions (ranging from 1.5 m s-1 to 22.8 m s-1), and we increased the water pCO2 concentration twice by more than 1000 µatm for two of the seven experimental days. We develop a conceptual box model that incorporated the thermodynamics of the marine CO2 system. Surfactant concentrations in the sea surface microlayer (SML) ranged from 301 µg L-1 to 1015 µg L-1 (as Triton X-100 equivalents) with enrichments ranged from 1.0 to 5.7 in comparison to the samples from the underlying bulk water. With wind speeds up to 8.5 m s-1, surfactants in the SML can reduce the gas transfer velocity by 54%. Wind-wave tank experiments in combination with modelling are useful tools for obtaining a better understanding of the gas transfer velocities of CO2 across the air-sea boundary. The tank allowed for measuring the gas exchange velocity under extreme low and high wind speeds; in contrast, most previous parametrizations have fallen short because measurements of gas exchange velocities in the field are challenging, especially at low wind conditions. High variability in the CO2 transfer velocities suggests that gas exchange is a complex process not solely controlled by wind forces, especially in low wind conditions.